From Consumerism to Sustainability: discussing the attractiveness of “borrowing shop” to Chinese customers - lou, yingzi (2017)
This research aims to discuss the attractiveness of “borrowing shop” to customers in China. To discuss this topic, there are three objectives including what the factors motivating these consumers to try the borrowing shops might be, what the factors dissuading them from trying the borrowing shops might be and how marketing mix could be used to increase the attractiveness of the borrowing shops in China. During the research, in-depth interview is used. Then the data are collected to get some relative findings before discussion. This research found that self-desire, external compensations, ego-enhancements, social pressure and taking preventive measures might be the factors motivating the Chinese consumers to try the borrowing shops while value conflict and distrust might be viewed as two main factors which might dissuade the Chinese consumers from trying the borrowing shops. As for marketing mix which could be used, the borrowing shops might need to focus on different aspects including products’ quality and functions, nice services, acceptable price, accessible locations, attractive advertising and the use of social medias.